Emotional eating in relation to gastrointestinal symptoms and burnout among young women during the pandemic - Gulay YILMAZEL; Emre Keles; Nur Pinar Ayaz (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundThe emergence of the coronavirus disease (COVID-19), created unique constraints in everyday life. Emotional eating is a known phenomenon in disasters and is markedly associated with gastrointestinal symptoms. In this study, the aim was to assess the relationship of gastrointestinal symptom severity and COVID-19 burnout with emotional eating among young women during the pandemic disaster. MethodsA cross-sectional study approach was used to allow 462 young women participants in this study. The design of the questionnaires was based on demographics, health behaviors, Gastrointestinal Symptom Severity Scale, Emotional Eating Scale and COVID-19 Burnout Scale. Data were analyzed using percentages, mean values, independent t-test, chi-squared test. The hierarchical multiple regression analysis was performed for predicting risk factors of emotional eating. Significance levels were set at the 5% level. ResultsOf the women, 73.8% were emotional eaters. The level of COVID-19 burnout was moderate with mean score of 29.4±11.1 and emotional eating total score was 21.0±8.1. Increased number of meals, increased weight gain and shorter sleep time were significantly associated with emotional eating (p<0.05). Participants with more than three meals per day were more likely to be emotional eaters (Beta=4.26). The regression model showed that indigestion and COVID-19 burnout were strong risk factors of emotinal eating (p<0.05). ConclusionsThis study demonstrated that indigestion and COVID-19 burnout were strong risk factors of emotinal eating. Emotional eating could pose an additional health burden to young women in the form of poor food choices.